Digital techniques for wideband receivers - Tsui, James Bao-yen (SciTech radar and defense series., 2004)
Wideband receivers were the domain of electronic warfare (EW) systems. With the advent of modern communications and ever increasing bandwidth requirements, the differences between EW and communication receivers become smaller and smaller. The purpose of this book is to introduce digital signal processing approaches that are applicable to wideband receiver designs. Its emphasis is on techniques rather than theoretical discussions. It is written primarily for researchers in EW and communications areas and is presented at a senior or graduate school engineering level. Many examples are presented and a comprehensive bibliography is offered at the end of each chapter. Many computer programs, written in MATLAB, are included to help the reader understand the problems and design of a wideband receiver.